Molecular cloning and characterization of the human PED/PEA-15 gene promoter reveal antagonistic regulation by hepatocyte nuclear factor 4alpha and chicken ovalbumin upstream promoter transcription factor II - Ungaro, Paola; Teperino, Raffaele; Mirra, Paola; Cassese, Angela; Fiory, Francesca; Perruolo, Giuseppe; Miele, Claudia; Laakso, Markku; Formisano, Pietro; Beguinot, Francesco (The Journal of biological chemistry, 2008)
Overexpression of the ped/pea-15 gene in mice impairs glucose tolerance and leads to diabetes in conjunction with high fat diet treatment. PED/PEA-15 is also overexpressed in type 2 diabetics as well as in euglycemic offspring from these subjects. The cause(s) of this abnormality remains unclear. In the present work we have cloned and localized the promoter region of the human PED/PEA-15 gene within the first 230 bp of the 5(R)-flanking region. A cis-acting regulatory element located between -320 and -335 bps upstream the PED/PEA-15 gene transcriptional start site (+1) is recognized by both the hepatocyte nuclear factor 4alpha (HNF-4alpha) and the chicken ovalbumin upstream promoter transcription factor II (COUP-TFII), two members of the steroid/thyroid superfamily of transcription factors, both of which are involved in the control of lipid and glucose homeostasis. HNF-4alpha represses PED/PEA-15 expression in HeLa cells, whereas COUP-TFII activates its expression. In hepatocytes, the activation of PED/PEA-15 gene transcription is paralleled by the establishment of a partially dedifferentiated phenotype accompanied by a reduction in mRNA levels encoded by genes normally expressed during liver development. Cotransfection of HeLa cells with a reporter construct containing the PED/PEA-15 response element and various combinations of HNF-4alpha and COUP-TFII expression vectors indicated that COUP-TFII antagonizes the repression of the PED/PEA-15 gene by HNF-4alpha. Thus, at least in part, transcription of the PED/PEA-15 gene in vivo is dependent upon the intracellular balance of these positive and negative regulatory factors. Abnormalities in HNF-4alpha and COUP-TFII balance might have important consequences on glucose tolerance in humans.